Finding the missing piece of the aquatic plastic pollution puzzle: Interaction between primary producers and microplastics. Issue 4 (5th June 2017) - Yokota, Kiyoko; Waterfield, Holly; Hastings, Cody; Davidson, Emily; Kwietniewski, Edward; Wells, Britney
Abstract: Mounting evidence of global plastic pollution has prompted many studies of its potential effects on aquatic ecosystems. In particular, most research has focused on organismal responses to microplastics and the effects of microplastics when introduced as food. However, there has been far less research into the possible effects of microplastics on primary producers. In this review, we document the available evidence for possible effects from the literature and from a laboratory experiment using cyanobacteria and microplastic fragments. Our review shows that primary producer–microplastic interactions can alter algal photosynthesis, growth, gene expression, and colony size and morphology, possibly via adhesion and/or transfer of adsorbed pollutants from microplastics; and, these effects could be transferred up the food web, including to humans. We recommend that the effects of microplastics on primary producers be incorporated into microplastic research to better understand its full effects on freshwater and marine ecosystems.